DNA BARCODING ANGIOSPERMS: IDENTIFYING PORTULACA SPECIES USING MATK AND ITS2 - Yu, Hai Ping (2018)
Weeds are invading agricultural farms causing impacts to both industry and consumers, not only in terms of economic loss through crops reduction and increase of labour costs in elimination of weeds but also in their invasive characteristic which destroy the native biodiversity in the farm. DNA Barcoding is a fast and accurate species identification system which utilizes standardize short DNA sequence as an universal barcode known as marker. Earlier stage of invasive weeds identification can be done with the ease by DNA Barcoding and thus serve to inform weed management for effective solution. DNA barcoding while being a widely used method, has had problems in its use such as lack of consensus on gene loci. In this study, Portulaca oleracea (both ornamental and wildtype) and Portulaca grandiflora were sampled for DNA Barcoding with the use of matK and ITS2 loci respectively whereby the efficiency of the gene loci were evaluated based on assessments of sequence quality, and levels of species discrimination. DNA of all three replicates of each of the Portulaca species were successfully extracted in triplicates using the Edwards method. Both matK and ITS2 were successfully amplified and sequenced followed by NCBI BLAST. The BLAST results showed identification to species level while the unexpected hit of ornamental P. oleracea (ITS2 amplicon) to P. umbraticola revealed the limitation of DNA barcoding which is incomplete reference sequence from public database. The phylogeny tree implies capability of both matK and ITS2 in discriminating Portulaca species as unique clades are formed for each taxon